Penerapan Model Decision Tree Menggunakan Python Untuk Prediksi Faktor Dominan Penyebab Penyakit Stroke - Permana, Baiq Andriska Candra; Sadali, Muhamad; Ahmad, Ramli (Infotek: Jurnal Informatika dan Teknologi, 2024)
Stroke is known as a disease caused by rupture of blood vessels in the brain or blockage of blood vessels in the brain. Disruption of the blood supply to the brain can result in damage to brain cells which results in damage to brain function. According to the World Health Organization (WHO) stroke is one of the highest causes of death worldwide, because almost 85% of the causes of death in the world are due to stroke. Current developments in science and technology require research to analyze stroke patient data so that the dominant factors that lead to stroke can be identified. This is an initial step that can be taken to address these problems to reduce the risk of death caused by stroke. In this study, the analysis was carried out by implementing a decision tree algorithm using python because the decision tree has good accuracy 91% in making predictions. With the decision tree formed from this algorithm, it will be easy to see the symptoms, starting from those who are most at risk to those who have the lowest risk of causing stroke